2016
DOI: 10.1088/1757-899x/160/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Properties of Coal Bottom Ash (CBA) from Tanjung Bin Power Plant

Abstract: The objective of this study is to determine the physical and chemical characteristics of Coal Bottom Ash (CBA) obtained from Tanjung Bin Power Plant Station and compare them with the characteristics of natural river sand (as a replacement of fine aggregates). Bottom ash is the by-product of coal combustion during the electricity generating process. However, excess bottom ash production due to the high production of electricity in Malaysia has caused several environmental problems. Therefore, several tests have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…), but with greater content of unburned carbon. Fly ash particles are spherical and alkaline in nature [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…), but with greater content of unburned carbon. Fly ash particles are spherical and alkaline in nature [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Coal bottom ash (CBA) is the by-product of the pulverized coal in power plants. It has large particle size and porous in nature [6] as shown in Figure 1. Its application in the field of civil engineering has the great environmental advantages, which are noteworthy in the sustainability of natural resources [7].…”
Section: Introductionmentioning
confidence: 99%
“…The BA represented comparatively lower specific gravity and higher water absorption compared with the granite aggregate. Ramzi et al [35] have reported similar results of specific gravity. The higher carbon content in BA may result in lower specific gravity [36].…”
Section: Materials and Methodology 21 Aggregate Characterisationmentioning
confidence: 56%